The impact of Craigslist's entry on competing employment websites - Vera Brenčič (IZA Journal of Labor Economics, 2016)
Craigslist, a website that hosts job- and help-wanted ads, expanded rapidly across the states in the USA over a very short period of time, thereby changing abruptly the market structure faced by competing employment websites. We exploit this abrupt change to evaluate its impact on competing websites' online traffic and pricing. We find that Craigslist's entry was associated with a decrease in the number of visitors that an average competing employment website attracted and with a decrease in the number of pages an average visitor reviewed during a typical visit. We also find that employment websites lowered some of the fees they charged their users. Overall, these findings offer one explanation for why Craigslist, despite its popularity, had little effect on the unemployment rate in the labor markets it entered: the entry of Craigslist cannibalized online traffic at competing employment websites.
Keywords: J20; L10; L86; 330; Entry response; Employment website; Craigslist